Identification of Molecular Markers of Clozapine Action in Ketamine-Induced Cognitive Impairment: A GPCR Signaling PathwayFinder Study - Agata Korlatowicz (MDPI AG, 2021)
Background: Cognitive disorders associated with schizophrenia are closely linked to prefrontal cortex (PFC) dysfunction. Administration of the non-competitive NMDA receptor antagonist ketamine (KET) induces cognitive impairment in animals, producing effects similar to those observed in schizophrenic patients. In a previous study, we showed that KET (20 mg/kg) induces cognitive deficits in mice and that administration of clozapine (CLZ) reverses this effect. To identify biochemical mechanisms related to CLZ actions in the context of KET-induced impairment, we performed a biochemical analysis using the same experimental paradigm—acute and sub-chronic administration of these drugs (0.3 and 1 mg/kg). Methods: Since the effect of CLZ mainly depends on G-protein-related receptors, we used the Signaling PathwayFinder Kit to identify 84 genes involved in GPCR-related signal transduction and then verified the genes that were statistically significantly different on a larger group of mice using RT-PCR and Western blot analyses after the administration of acute and sub-chronic drugs. Results: Of the 84 genes involved in GPCR-related signal transduction, the expression of six, βarrestin1, βarrestin2, galanin receptor 2 (GalR2), dopamine receptor 2 (DRD2), metabotropic glutamate receptor 1 (mGluR1), and metabotropic glutamate receptor 5 (mGluR5), was significantly altered. Since these genes affect the levels of other signaling proteins, e.g., extracellular signal-regulated kinase 1/2 (ERK1/2), G protein-coupled receptor kinase 2 (Grk2), and G protein-gated inwardly rectifying potassium 3 (Girk3), we determined their levels in PFC using Western blot. Most of the observed changes occurred after acute treatment with 0.3 mg/kg CLZ. We showed that acute treatment with CLZ at a lower dose significantly increased βarrestin1 and ERK1/2. KET treatment induced the upregulation of βarrestin1. Joint administration of these drugs had no effect on the βarrestin1 level. Conclusion: The screening kit we used to study the expression of GPCR-related signal transduction allowed us to select several important genes affected by CLZ. However, the obtained data do not explain the mechanism of action of CLZ that is responsible for reversing KET-induced cognitive impairment.